Proof of quantum mechanical H-theorem beyond binary collisions in quantum gases. (9th October 2018) - Das, Bandita; Biswas, Shyamal
Abstract: We have proved the quantum mechanical H-theorem for dilute Bose and Fermi gases by generalizing the quantum statistical Boltzmann equation for all possible many-body elastic collisions among the particles in the quantum gases within the Lippmann–Schwinger formalism. Previous study by Pauli did almost the same only for binary elastic collisions. We are considering all possible many-body elastic collisions for the current study. Our proof offers a better understanding of the foundation of the second law of thermodynamics for quantum gases.